Transthoracic device closure of perimembranous ventricular septal defect via a small left intercostal incision in children - Xie, Linfeng; Zhang, Guican; He, Jian; Shen, Yanming; Liao, Dongshan; Chen, Liangwan; Xu, Fan (Frontiers in Cardiovascular Medicine, 2023)
Background In children with perimembranous ventricular septal defect, surgical repair requires sternotomy and leaves unsightly scars, which can trigger long-term physical and psychological distress. However, transcatheter device closure is limited by vascular diameter, radiographic exposure, and expensive DSA equipment. We used an ultra-small left intercostal incision for transthoracic device closure to avoid the above problems and investigated its safety and feasibility by comparing it with surgical repair. Methods This study enrolled 358 children with perimembranous ventricular septal defect. Among them, 152 patients were treated by surgical closure and 206 by transthoracic device closure via an ultra-small left intercostal incision. Perioperative clinical data and postoperative follow-up results were collected and analyzed retrospectively. Results The success rate was similar (P = 0.265) in the two groups: 203/206 patients in the device group vs. 152/152 patients in the surgical group. The operative time, intensive care unit time, mechanical ventilation time, and postoperative hospital stay were significantly shorter in the device group than in the surgical group. Although the incision length of the device group (1.1 ± 0.2 cm) was significant shorter (P < 0.001) than that of the surgical group (6.7 ± 1.5 cm), there was no difference in hospitalization costs between the two groups (P = 0.099). Except for small residual shunt (16/206 vs. 3/152, P = 0.017), the incidence of complications in the device group was lower or equal to that in the surgical group, and all small residual shunt disappeared during follow-up. There was no thoracic deformity in the device group, compared with 11 cases in the surgery group during follow-up (P < 0.001). Conclusions Transthoracic device closure via an ultra-small left intercostal incision under transesophageal echocardiography guidance is safe and feasible. With appropriate indications, it can be a suitable alternative to surgical closure for treating perimembranous ventricular septal defect in children.